Carbon as a MEMS material: micro and nanofabrication of pyrolysed photoresist carbon. (23rd January 2008) - Wang, Chunlei; Zaouk, Rabih; Park, Benjamin Y.; Madou, Marc J.
Carbon, like Si, is an attractive and very versatile engineering material and is available in more structural varieties than Si. Carbon materials are already in use in a wide variety of applications because of their widely differing crystalline structures and properties, which enable very different physical, chemical, mechanical, thermal and electrical uses. Carbon-based Microelectromechanical Systems (MEMS) and Nanoelectromechanical Systems (NEMS), with sizes ranging from millimetre to nanometre, can provide solutions, alone or in combination with Si and other materials for microelectronics, nanoelectronics, sensors, miniaturised power systems, etc. In this review, Carbon-MEMS (C-MEMS) and Carbon-NEMS (C-NEMS) technology based on pyrolysis of patterned photoresist is reviewed. The fabrication process and the most promising applications are introduced.